Elaboração de um Jogo Digital Educacional sobre Saúde Bucal Direcionado para a População Infantil - Dotta, Edivani Aparecida Vicente [UNESP]; Campos, Juliana Alvares Duarte Bonini [UNESP]; Garcia, Patrícia Petromilli Nordi Sasso [UNESP] (APESB (Associacao de Apoio a Pesquisa em Saude Bucal), 2012)
Objective: The aim of this study was to develop an educational oral health digital game for 5-to-7-year-old children. Method: The game, called “Dr. Trata Dente”, was based on the approach to three different oral health-related topics: a) bacterial plaque and the main diseases caused by it; b) oral hygiene methods for bacterial plaque control; c) dental caries and preventive measures for this disease. These topics were discussed in sequential order in three different stages of the game. Dr. Trata Dente is represented by the figure of a little super-hero dentist, who talks to the children about oral health during the game. The game is sub-divided according to its propositions to the children, into an association game, a memory game and a coloring game. After its development, the game was evaluated by three professionals of each of the following areas: Dentistry, Pedagogy and Psychology (n=9), who verified the suitability of the concepts presented in the game as regards oral health, linguistic abilities worked with the children, fulfillment of the intended didactic criteria, and the playful aspect of the game. Results: According to the dentists, the dental concepts presented in the game are adequate. According to the pedagogues, the choice of a super-hero was correct and the given explanations are well elaborated, organized and have accessible language, although long. For the psychologists, the game has a potential positive effect on the children’s learning, but there should be more interaction of the character with the children. After this evaluation, changes were made in the game according to the professionals’ suggestions. Conclusion: It was concluded that in spite of the suggested alterations, the game is suitable for teaching oral health by means of children’s play.

Objetivo: Elaborar um jogo digital sobre saúde bucal para crianças de 5 a 7 anos. Método: O jogo, que recebeu o nome de Dr. Trata Dente, se baseou na abordagem de três diferentes tópicos sobre saúde bucal: a) a placa bacteriana e as principais doenças por ela causadas; b) os métodos de higiene bucal para controle da placa bacteriana, e c) a cárie dental e suas medidas preventivas. Esses tópicos foram expostos sequencialmente, em três diferentes fases do jogo. O Dr. Trata Dente é representado pela figura de um dentista super-herói mirim, que conversa com as crianças sobre saúde bucal durante o jogo. Este é subdividido segundo suas proposições junto às crianças: associação, memória e pintura. Após seu desenvolvimento, o jogo foi analisado por três profissionais de cada área: Odontologia, Pedagogia e Psicologia (n=9), os quais observaram a adequação dos conceitos apresentados em relação à saúde bucal, às capacidades linguísticas trabalhadas, ao atendimento dos critérios didáticos pretendidos e à ludicidade. Resultados: De acordo com os cirurgiões-dentistas, os conceitos odontológicos emitidos estão adequados. Segundo os pedagogos, a escolha de um super-herói foi acertada e as explicações dadas estão bem elaboradas, mostram-se organizadas e com linguagem acessível, porém longas. Para os psicólogos, o jogo apresenta potencialmente um efeito positivo sobre o aprendizado das crianças, mas o personagem deve interagir mais com elas. Após a avaliação, modificou-se o jogo segundo as sugestões dos profissionais. Conclusão: Apesar das alterações sugeridas, o jogo apresenta-se adequado para o ensino de saúde bucal por meio da brincadeira.
Development of an educational oral health digital game for children
Keywords: Education; Motivation; Oral health; Pre-school children; Play and Playthings; Educação; Motivação; Saúde bucal; Pré-escolares; Jogo e brinquedos